Assessing territorial vulnerabilities and spatial inequalities: the case of Portugal - Marques, Teresa Sá (2019)
The economic crisis of the past decade has exacerbated existing vulnerability problems in Europe, particularly in the southern countries. These relate to unemployment, poverty, housing conditions, access to basic services or insecurity issues, among others, and have affected particular groups as migrant or the elderly. Although the increase in quality of life is a transversal goal to cohesion and urban policies, the effects of vulnerability have only recently begun to be documented in scientific research. Generally, comparative vulnerabilities' assessments are based on limited (often economic) indicators or, if they are more comprehensive, on a limited territorial scale. Thus, they don't perform holistic analysis at national scale, nor comprehensive regional/municipal comparisons. Consequently, this paper presents a multivariate diagnosis of vulnerabilities at national scale, considering an array of indicators of quality of life in various domains as housing, health, accessibility, education, security or employment. Each indicator was geo-referenced and represented at municipal level, leading to the creation of indexes of vulnerability for each theme. An overall index of vulnerability combining all parcels was then composed through advanced statistical analyses' techniques. More than displaying territorial differences, this approach allows discussing different geographical realities within Portugal, and provide outputs for supporting planning policies concerning integration, social cohesion, urban equity, and the development of urban systems.